Pengaruh model Think-Pair-Share menggunakan pembelajaran berdiferensiasi terhadap keterampilan berkomunikasi peserta didik dalam pembelajaran IPAS di sekolah dasar - Nadhilla Andrianni; Idam Ragil Widianto Atmojo (Didaktika Dwija Indria, 2026)
This study examines the effect of the Think-Pair-Share (TPS) model integrated with differentiated learning on elementary students' written communication skills in Natural and Social Sciences (IPAS) learning. Using a quasi-experimental design with non-equivalent control group, the research involved 52 fourth-grade students from Cluster 1, Banjarsari District, Surakarta, divided into experimental and control classes. The experimental class implemented TPS with differentiated learning based on learning styles, while the control class used the number-heads-together model. Data were collected through pretest and posttest in the form of poster-making tasks and analyzed using t-test, N-Gain, and SmartPLS 4. Results showed significant differences (sig. 0.001 < 0.05) with the experimental class achieving higher mean scores (79.23) compared to the control class (52.12). SmartPLS 4 analysis revealed that the think phase predominantly influenced information accuracy with visual learners showing the highest impact (0.609); the pair phase had the strongest effect on writing structure clarity with kinesthetic learners dominant (0.499) and the highest coefficient (0.023); while the share phase primarily affected information accuracy with kinesthetic learners most influential (0.238). The integration of TPS model with differentiated learning proved effective in enhancing elementary students' written communication skills by accommodating diverse learning needs and preferences through constructivist, humanistic, and cognitive approaches.